Aging‐ and vascular‐related pathologies. (19th June 2018) - Wen, Shu Wen; Wong, Connie H. Y.
Abstract: Our aging population is set to grow considerably in the coming decades. In fact, the number of individuals older than 65 years will double by 2050. This projected increase in people living with extended life expectancy represents an inevitable upsurge in the presentation of age‐related pathologies. However, our current understanding of the impact of aging on a number of biological processes is unfortunately inadequate. Cardiovascular, cerebrovascular, and neurodegenerative diseases are particularly prevalent in the elderly population. Intriguingly, these pathologies are all associated with vascular dysfunction, suggesting that the process of aging can induce structural and functional impairments in vascular networks. Together with elevated cell senescence, pre‐existing comorbidities, and the emerging concept of age‐associated inflammatory imbalance, impaired vascular functions can significantly increase one's risk in acquiring age‐related diseases. In this short review, we highlight some current clinical and experimental evidence of how biological aging contributes to three vascular‐associated pathologies: atherosclerosis, stroke, and Alzheimer's disease.